A Tale of Two Countries: DiaSorin Molecular’s Rapid Response to the COVID-19 Pandemic - Tabb, Michelle M.; Minnucci, Giulia; Albano, Vincenzo (Frontiers in Cellular and Infection Microbiology, 2022)
In the summer of 2019, DiaSorin Molecular started designing a multiplex respiratory panel with pan-coronavirus detection as one of the planned targets. The R&D team in Gerenzano, Italy was already searching databases, performing alignments and assessing preliminary target regions for common coronavirus RT-PCR, including SARS and MERS-CoV. In December 2019, we were vigilant and following a cluster of pneumonia cases with undetermined etiology in Wuhan, China. As we now know, the cause of the respiratory infections was the new SARS-CoV-2 virus. DiaSorin Molecular swiftly responded in line with our heritage and company history in detecting emerging infectious diseases. Early in the pandemic and in record time, using research and development teams in both Italy and the U.S. together with the U.S. manufacturing team, we were able to develop and commercialize a new diagnostic test, Simplexa™ COVID-19 Direct, to detect SARS-CoV-2. Our unique platform allowed development of a rapid diagnostic test without the need for extraction reagents. Challenges with control materials, quarantines, clinical samples, raw materials and production were overcome and the entire company worked side by side for accelerated delivery of this assay to clinical labs in Europe, the U.S. and Canada.